External Integration and Organizational Innovation Capacity Moderate by The Confidence Level - Sidnei Gripa; Luciano Castro de Carvalho (Revista Eletrônica de Ciência Administrativa, 2018)
Supply chain integration allows competitive advantage with respect to the operational performance for all those involved in this process. This is already well consolidated in the literature. The existing gap is related to the integration of the supply chain and the innovation capacity of organizations, since according to several authors, there still isn't enough data to prove this relationship. This study aims to identify whether integration of customers and suppliers influence on the organizational innovation capacity. For this, a descriptive research with quantitative method was carried out, using primary data from a survey. The data were collected through an online questionnaire with 20 questions, containing dimensions on customer and supplier involvement in product development process, trust and innovation capacity. Data were collected from 86 companies of the processing industry of varying sizes. The data were analyzed by structural equation modelling using SmartPLS software. The results indicate that the customer engagement influences 0.52 on organizational innovation capacity, but the involvement with suppliers, as well as moderation of trust about these relationships were not significant. It is concluded that the supply chain integration, mainly with the involvement of the costumers, influences the innovation capacity.